Penerapan Media Aplikasi Zoom Meeting Dalam Meningkatkan Prestasi Belajar pada Mata Pelajaran Al-Qur’an Hadis Siswa Kelas IX MTs Swasta Al-Washliyah Stabat - Khairil Anwar; Fauzan Azmi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2020)
This study raises the issue of lack of effectiveness and efficiency in using the Al-Qur'an Hadith learning media during the current pandemic. Al-Quran Hadith lessons can be developed through the Zoom Meeting application. The purpose of this study was to train the skills of reading the Koran orally and in writing to improve the ability of the quality values ​​of faith and Islamic knowledge of class IX students of MTs Swasta AL-Washliyah Stabat. This research is a classroom action research (CAR) (Syahbuddin AR:2012). with the implementation of the action research model in the form of a spiral and one cycle to the next from (Elfanany, 2013:58) development procedure which has four stages. The procedures for this research were planning, action, observation, and reflection. This research took 5 months, from January to June 2020. The subjects in this study were grade IX students at Private MTs AL-Washliyah Stabat with a total of 40 students. The data analysis technique in this research is qualitative data analysis and quantitative descriptive data analysis. Data collection techniques used instruments, interviews, observation and self-regulation skills training. The results of the research on the application of the zoom meeting application media in improving learning achievement in Al-Qur'an Hadith lessons in class IX students at Private MTs AL-Washliyah Stabat. Judging based on the results in the first cycle to the third cycle, the results were obtained. In the first cycle, the percentage of completeness was 63.64 %, an increase of 7.8% from the pre-cycle. In the second cycle, the percentage of mastery learning was 78.8%. There was another increase of 15%. from the first cycle, and in the third cycle achieved learning completeness of 90.3% increased from the second cycle. So from pre-cycle to cycle III there is an increase in the level of 33.7%. The test results of students' scores have met the Minimum Criteria for Completeness (KKM) which is 70 for Al-Quran Hadith subjects and has achieved a very effective and efficient classification.